The Chamber - Grisham, John (London Arrow, 1994)
A thriller about a rookie lawyer defending a member of the Ku Klux Klan who has been on Death Row for 23 years and faces the gas chamber. The lawyer hates his client's racist views, but as the case develops, it appears that his client may be innocent.
Keywords: Death row inmates -- Mississippi -- Bombings -- Mississippi--Greenville -- Ku Klux Klan (1915- )